A ONE-ON-ONE READING CLINIC FOR BEGINNING READERS: A DESCRIPTIVE CASE STUDY CONDUCTED IN ELEMENTARY SCHOOL IN LEMBANG - Sevia Putri Hastuti Juntara; Martina Mulyani (English Education Department of STKIP Pasundan, 2024)
Literacy is crucial for the height of a nation’s civilization. However, Indonesia’s literacy rate is still regarded as poor. To address the problem, Kemdikbud creates Kamjar (Kampus Mengajar), a program for college students to help relieve literacy issues in rural areas. Given that many students in remote areas are still illiterate despite having reached school age, the study created reading clinics to encourage students to learn to read by embracing personalized learning principles. Its purpose is to find out how one-on-one reading clinics can assist students who struggle with reading. Four students of an elementary school in Lembang West Jave were selected to participate in the study. Each one has a different age, personality, and different literacy skills. The instructions for those four students were created in such a way as to satisfy their needs. Employing a case study as the design of the research, the study utilized observation and interviews as data collection. The result of the study showed that one-on-one reading clinic can act as a good strategy for helping inconsistent struggling readers. However, collaboration with other peers is still needed to help the beginning readers assess their achievements, agency, and ownership over their learning.